Popularization of classical music performed by the "Johann Strauss" orchestra - Mitic, Marjan D. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2025)
Rieu’s career as a commercial artist began in 1993 in the Netherlands. His most significant success so far was in Australia, where since 2007 marketing campaigns and annual tours have made Rieu one of the most memorable artists and performers. Rieu was among the best-selling artists in any musical genre. As a performer, Rieu is a leader in elaborate performances that includes great architectural replicas and props, costumes, dancers, easy comedy and jokes with the audience. The critique of Rieu’s practices is mainly derived from the high artistic sector of classical music. This sector represents a special and prescriptive way of appreciation that resists adaptation to the contemporary and pluralistic cultural environment. Combined with open criticism, this suggests that classical high art music attempts to define, or redefine itself, as a reaction against the gradual inclusion of commercial and national elements.